An Engineered Distant Homolog of Pseudomonas syringae TTSS Effector From Physcomitrella patens Can Act as a Bacterial Virulence Factor - Piechocki, Marcin; Giska, Fabian; Koczyk, Grzegorz; Grynberg, Marcin; Krzymowska, Magdalena (Frontiers in Microbiology, 2018)
Pseudomonas syringae pv. phaseolicola is the causative agent of halo blight in common bean (Phaseolus vulgaris). Similar to other pathogenic gram-negative bacteria, it secrets a set of type III effectors into host cells to subvert defense mechanisms. HopQ1 (for Hrp outer protein Q) is one of these type III effectors contributing to virulence of bacteria. Upon delivery into a plant cell, HopQ1 undergoes phosphorylation, binds host 14-3-3 proteins and suppresses defense-related signaling. Some plants however, evolved systems to recognize HopQ1 and respond to its presence and thus to prevent infection. HopQ1 shows homology to Nucleoside Hydrolases (NHs), but it contains a modified calcium binding motif not found in the canonical enzymes. CLuster ANalysis of Sequences (CLANS) revealed that HopQ1 and alike proteins make a distinct group of putative NHs located distantly from the classical enzymes. The HopQ1 – like protein (HLP) group comprises sequences from plant pathogenic bacteria, fungi and lower plants. Our data suggest that the evolution of HopQ1 homologs in bacteria, fungi and algae was independent. The location of moss HopQ1 homologs inside the fungal clade indicates a possibility of horizontal gene transfer between those taxa. We identified a HLP in the moss Physcomitrella patens. Our experiments show that this protein (referred to as PpHLP) extended by a TTSS signal of HopQ1 promoted P. syringae growth in bean and was recognized by N. benthamiana immune system. Thus, despite the low sequence similarity to HopQ1 the engineered PpHLP acted as a bacterial virulence factor and displayed similar to HopQ1 virulence properties.